Phase Transparent Demultiplexer for QPSK Signal Based on Nonlinear Response in a Double-Pass Architecture - Yu-Hsiang Wen; Jia-Wei Ho; Kai-Ming Feng (IEEE Photonics Journal)
We propose and experimentally demonstrate an optical modulation format converter from a 25-Gbps quadrature phase-shift keying (QPSK) signal to two 12.5-Gbps binary phase-shift keying (BPSK) signals in a double-pass configuration, which is achieved by four-wave mixing in a single highly nonlinear fiber. The phase logic of the original QPSK signal is preserved on both of the converted BPSK signals. The clear constellation diagrams and the satisfactory bit-error-rate (BER) performance are successfully obtained both in numerical simulation and experimental demonstration. Moreover, the tolerance of phase mismatch among pumps and signals in the proposed format converter is also investigated.